Pemberdayaan Ekonomi Melalui Program BJB Mesra dalam Meningkatkan Kesejahteraan Masyarakat - Imas Siti Jubaedah; Dadang Kuswana; Putri Diesy Fitriani (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
The economic crisis caused by the Covid-19 pandemic has had an impact on the continuity of Micro, Small, and Medium Enterprises (MSMEs). The financing programs offered by banks and the government have not been fully accessible to all business actors, so people are interested in applying for capital to loan sharks. Thus, bank bjb issued the BJB Mesra program in order to prevent people from being entrapment of loan sharks. This study aims to explain the BJB Mesra program in improving community welfare including planning, implementing and impacting the program. The research method used is a descriptive study with a qualitative approach because it produces data that can be observed empirically. Robert Chambers' Theory of Empowerment suggests that empowerment is a concept of economic development that summarizes social values. The results showed that the BJB Mesra program is a capital cost assistance to the community around the house of worship. This program is an initiation from the Governor of West Java in order to realize the West Java Champion of Inner Birth. The implementation of this program consists of submission, training and selection, administrative process, second training, analysis process, decision process, disbursement and assistance. The impact of this program can be felt directly by the community, especially in reducing poverty due to the entanglement of loan sharks.